Guía motivacional de juegos tradicionales ecuatorianos para las escuelas de la Parroquia Eloy Alfaro, Cantón Latacunga Provincia de Cotopaxi durante el año lectivo 2011- 2012. - Zumba Chiluisa, Jorge Fabián (2013)
The present research is based on analyze of Ecuadorian Traditional Games and its impact on psychomotor development of children in schools Eloy Alfaro Parish, Latacunga Canton, Cotopaxi Province during school years 2012-2013”. The problem was raised on the low children motivation on movement control around learning in schools and little practice of Ecuadorians traditional games. The research was philosophical, pedagogical, legal and theoretical base. We used theme thud of field research, since the data which were collected directly in the real and core relational study that assessed the degree of relationship between two variables of the investigation. The results of these studies concluded on the importance of valuing the traditional games Ecuadorian Educational practice thus allowing the children`s psychomotor development of Eloy Alfaro Parish, Latacunga Canton, Cotopaxi Province during the school years 2012-2013 to improve school performance and social development. Finally, we presented a proposed Traditional Games Ecuadorian in order to guide teachers who can be apply in schools.